THE CONCEPT OF GUIDANCE FOR CHILDREN IN CONFLICT WITH THE LAW WHO HAVE SERVED CRIMINAL SENTENCES IN SPECIAL CHILD GUIDANCE INSTITUTIONS (LPKA) - Fitriah Fitriah; Ferry Fathurokhman; Mohamad Noor Fajar Al Arif (Universitas Dharmawangsa Medan, 2025)
The limited number of experts and professionals in the LPKA environment to provide guidance to ABH so that they are replaced by LPKA officers to carry out ABH guidance causes not optimal educational development, personality development, and independence development for ABH, and results in the repetition of criminal acts by ABH who have just been released from LPKA. The problem discussed is how the concept of the Child Special Development Institution (LPKA) is associated with the future of Children in Conflict with the Law (ABH), and how the implementation of guidance for Children in Conflict with the Law (ABH) which has served a sentence at the Child Special Development Institution (LPKA). This type of research is normative legal research. Conclusion: ((1) The concept of LPKA is associated with the future of ABH, until now it has not been able to fully carry out its ideal function as a rehabilitative and educative institution. This is due to various fundamental limitations, including the lack of involvement of professional experts in the fields of psychology, education and social affairs, as well as a coaching approach that is still monotonous and administrative in nature; (2) The implementation of coaching for children in conflict with the law (ABH) who have received punishment in the Special Development Institution for Children (LPKA) has so far been ineffective, this is due to failures that stem from various fundamental problems, especially the lack of involvement of professional experts in the coaching process. Suggestions: (1) The Ministry of Immigration and Corrections is expected to implement a strategic policy by placing professionals equally experts in all LPKA in Indonesia. The existence of child psychologists, social counselors, special teachers, and skills trainers is a crucial element in forming a comprehensive coaching system that is responsive to the needs of growth and development and psychological recovery of ABH; (2) The Ministry of Immigration and Corrections in charge of the Child Special Development Institution (LPKA) is expected to reformulate the coaching policy for ABH in a more progressive, comprehensive, and oriented towards the recovery of children as whole individuals. The coaching policy needs to integrate character education approaches, psychosocial interventions, counseling, mental recovery, and skills training based on disciplinary and humanitarian values.